((The Impact of Organizational Values on achieve Strategic Success Analytical Research in the Iraq Ministry of Oil )) - محمد, نسرين جاسم; عصاد, مصطفى عبد العباس (Journal of Economics and Administrative Sciences, 2018)
This study aims to determine the impact of organization values as an independent variable across its dimensions (organization management values, organization mission values, relations management values, and environment management values) on achieve the strategic success which is the dependent variable and include its dimensions  (environmental analysis, creative thinking, strategic decision, effective implementation, and leadership capacities). The study is conducted in the Iraq Oil Ministry. It deployed the analytical descriptive approach. It focuses on the study problem enquiries throughout addressing several principal and sub-hypothesizes in regards to cause and effect relationship. To achieve this result a sample of the subject community has been studied. The sample has ( 60 ) high rank leaderships selected based on comprehensive and elected method. The researcher uses surveys, interviews, and observations to collect the required information. The researcher distributed ( 67) survey on the samples community, ( 60 ) viable surveys were submitted. The information then processed through (SPSS) using natural distribution, percentages, medium, standard deviation, and (Person) coefficient correlation, and simple and multi-liner regression. The research concludes that the hypotheses are true.The research finds that there is a positive correlation relationship between the organizationals values and the strategic success. The research finds that, among other dimension, organizational environment management is the most influential on the strategic success. The research came out with several recommendations. Among them are: investing in active relationship between organizational value and strategic success, promoting the origination investment in the organizational value set, this serves as a pattern of good employees' conduct and entrepreneurship method that reveals the organization reputation in such a way distinguishes the organization from others to reach high levels of strategic success.  The organization then deploys values in a collective manner to achieve the strategic success and be able to develop and grow amidst of environmental uncertainty, and deepen the organization interest in its strategic success.